2020
DOI: 10.1101/2020.02.17.953141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Basal forebrain-derived acetylcholine encodes valence-free reinforcement prediction error

Abstract: Acetylcholine (Ach) is released by the cholinergic basal forebrain (CBF) throughout the cortical mantle and is implicated in behavioral functions ranging from arousal to attention to learning. Yet what signal ACh provides to cortex remains unresolved, hindering our understanding of its functional roles. Here we demonstrate that the CBF signals unsigned reinforcement prediction error, in contrast to dopamine (DA) neurons that encode reward 25 prediction error. We show that both CBF neuronal activity and acetylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 48 publications
8
55
4
Order By: Relevance
“…Plasticity related to learning has also been observed in cholinergic neurons in the basal forebrain complex during aversive trace conditioning, such that after several training days, neuronal activity spans the delay between CS and US ( Guo et al, 2019 ). Additionally, a recent study suggested that ACh may signal a valence-free reinforcement prediction error ( Sturgill et al, 2020 ). Future studies on the selective inputs to NBM to BLA cholinergic neurons would be of interest to identify the links between brain areas involved in prediction error coding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasticity related to learning has also been observed in cholinergic neurons in the basal forebrain complex during aversive trace conditioning, such that after several training days, neuronal activity spans the delay between CS and US ( Guo et al, 2019 ). Additionally, a recent study suggested that ACh may signal a valence-free reinforcement prediction error ( Sturgill et al, 2020 ). Future studies on the selective inputs to NBM to BLA cholinergic neurons would be of interest to identify the links between brain areas involved in prediction error coding.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent study suggested that ACh may signal a valence-free reinforcement prediction error (Sturgill et al, 2020). Future studies on the selective inputs to NBM to BLA cholinergic neurons would be of interest to identify the links between brain areas involved in prediction error coding.…”
Section: Bla Ach Signaling and Camkiiα Cell Activity Are Related To Cmentioning
confidence: 99%
“…Acetylcholine (ACh) is a neurotransmitter and neuromodulator that is released throughout the mammalian cortex at times of alertness and arousal ( Teles-Grilo Ruivo et al, 2017 ) in order to promote learning and memory ( Hasselmo, 2006 ), modulate sensory perception ( Pinto et al, 2013 ), gate plasticity ( Morishita et al, 2010 ; Rasmusson, 2000 ), and enhance the detection of salient sensory cues and reinforcement ( Parikh et al, 2007 ; Sarter et al, 2009 ; Sarter et al, 2014 ; Sturgill et al, 2020 ). Most cortical ACh originates from subcortical nuclei in the basal forebrain Mesulam, 1995 whose long-range axons innervate broad regions of cortex and release ACh to modulate cortical function over fast and slow time scales ( Sarter et al, 2009 ; Picciotto et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acetylcholine (ACh) is a neurotransmitter and neuromodulator that is released throughout the mammalian cortex at times of alertness and arousal 1 in order to promote learning and memory 2 , modulate sensory perception 3 , gate plasticity 4,5 , and enhance the detection of salient sensory cues and reinforcement 69 . Most cortical ACh originates from subcortical nuclei in the basal forebrain 10 whose long-range axons innervate broad regions of cortex and release ACh to modulate cortical function over fast and slow time scales 7,11 .…”
Section: Introductionmentioning
confidence: 99%